The diverse roles of the eIF4A family: you are the company you keep. (23rd January 2014) - Lu, Wei-Ting; Wilczynska, Anna; Smith, Ewan; Bushell, Martin
Abstract : The eIF4A (eukaryotic initiation factor 4A) proteins belong to the extensive DEAD-box RNA helicase family, the members of which are involved in many aspects of RNA metabolism by virtue of their RNA-binding capacity and ATPase activity. Three eIF4A proteins have been characterized in vertebrates: eIF4A1 and eIF4A2 are cytoplasmic, whereas eIF4A3 is nuclear-localized. Although highly similar, they have been shown to possess rather diverse roles in the mRNA lifecycle. Their specific and diverse functions are often regulated and dictated by interacting partner proteins. The key differences between eIF4A family members are discussed in the present review.